IDENTIFIKASI DESA MANDIRI ENERGI - Purwoko, Ahmad Taufiq, (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The objective of the research was to identify the existing condition of the self-help energy village in Tanjung Harjo, Grobogan District, Central Java. The study found, firstly, it was difficult to change the planing culture from rice planting to Jatropa Curcus; secondly, it was brothersome to find the germ of the Jatropha Curcus; thirdly, for farmer it was not clear and uncertain about the economic prospect of Jatropha Curcus. It is necessarily had to investigate further research to answer, that the self-help energy village program unsuccessfully implemented comparing based on difference village and district.